DESIGN AND FABRICATION OF PVA-BASED RELATIVE HUMIDITY SENSOR USING THICK FILM TECHNOLOGY - Martadi, Supeno
This study discusses the design and fabrication of relative humidity sensors with Polyvinyl Alcohol (PVA) as a sensing layer using thick film technology. The design is optimized to produce the ideal geometry according to the limitations of thick film technology. The sensor fabrication process uses a screen printing techniques on an Alumina (Al2O3) substrate with silver (Ag) as a material for its conductor path. PVA deposition as a sensing layer is done by the spin coating method. Sensor fabrication test results are carried out by varying 5 humidity points in the chamber with a hygrometer as a reference. Based on the test results it is known that the sensor shows a response to humidity in the form of resistance value, if the humidity in the chamber increases, the sensor resistance value will decrease. Variations in the addition of the composition of SnO2 on the sensing layer were 1: 1 and 1: 2. Addition of SnO2 to PVA can desrease the reading of resistance values, decrease sensitivity and can increase the sensor response to humidity changes. FTIR results show that the addition of APS and SnO2 does not affect the structure of the PVA, this indicates that there is no chemical reaction between PVA, APS and SnO2. The relatively high value of PVA-based humidity sensor resistance can be reduced by mixing PVA with metal oxides in this study using SnO2.